2023
DOI: 10.1039/d2sc02856e
|View full text |Cite
|
Sign up to set email alerts
|

Structural features of interfacial water predict the hydrophobicity of chemically heterogeneous surfaces

Abstract: The hydrophobicity of an interface determines the magnitude of hydrophobic interactions that drive numerous biological and industrial processes. Chemically heterogeneous interfaces are abundant in these contexts; examples include the surfaces...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 76 publications
(196 reference statements)
0
14
0
Order By: Relevance
“…In Figure a, we observe a pronounced peak in PC3 at θ ≈ 50° that cannot be directly attributed to icosahedral or tetrahedral structures. Previous work has suggested that features at θ ≈ 50° stem primarily from a small population of five-coordinate water molecules. , These authors demonstrate higher P 3 b (50°) in five-coordinate waters than in four-coordinate waters. Additionally, PC3 presents a diffuse, positive amplitude for θ > 120°.…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…In Figure a, we observe a pronounced peak in PC3 at θ ≈ 50° that cannot be directly attributed to icosahedral or tetrahedral structures. Previous work has suggested that features at θ ≈ 50° stem primarily from a small population of five-coordinate water molecules. , These authors demonstrate higher P 3 b (50°) in five-coordinate waters than in four-coordinate waters. Additionally, PC3 presents a diffuse, positive amplitude for θ > 120°.…”
Section: Resultsmentioning
confidence: 69%
“…As discussed in Section , we attribute PC3 primarily to the effect of a small population of five-coordinate waters. Furthermore, we note that Dallin et al found the population of five-coordinate waters to be predictive of solvation energetics, namely, the hydration free energy at self-assembled monolayer surfaces (SAMs) . The resulting projection of a given system’s differential three-body angle distribution onto PC3 quantifies the portion of three-body angles corresponding to a five-coordinate water molecule.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations